ESG Disclosure and Firm Value: The Moderating Role of Competitive Advantage - Muadah, Rania; Rohman, Abdul (Dinasti Publisher, 2026)
Environmental, social, and governance (ESG) disclosure has been increasingly recognized as a significant determinant of firm value; however, its effectiveness is believed to be influenced by the firm's internal conditions, particularly its competitive advantage. This study aims to examine the effect of ESG disclosure on firm value and to investigate the moderating role of competitive advantage in this relationship. The research sample comprises companies listed on the ESG Quality 45 KEHATI Index of the Indonesia Stock Exchange over the period 2021–2024. Moderated regression analysis was employed using EViews software. The results indicate that ESG disclosure positively affects firm value, suggesting that sustainability transparency enhances stakeholder trust and drives higher market valuations. Furthermore, competitive advantage is found to significantly strengthen the positive effect of environmental, ESG disclosure on firm value, indicating that firms with stronger competitive positions are better able to leverage their sustainability disclosure in creating value for stakeholders. These findings enrich the application of stakeholder theory by establishing that competitive advantage serves as a critical boundary condition that determines the effectiveness of environmental, social, and governance disclosure in enhancing firm value.